Healthcare Professionals’ Knowledge of the Brazilian Guidelines for Organ Maintenance in Potential Deceased Donors - Costa, Juliana Martins; da Silva Knihs, Neide; Garcia, Mayara Costa (Brazilian Journal of Transplantation, 2026)
Objectives: To evaluate the knowledge of healthcare professionals regarding the Brazilian Guidelines for Organ Maintenance in Potential Donors. Methods: A quantitative, descriptive, and exploratory study. Participants included healthcare professionals working in the National Transplant Center, State Transplant Centers, Organ Procurement Organizations, Intra-Hospital Organ and Tissue Donation Committees for Transplantation, and critical care units. The study took place from November 2024 to March 2025, and data collection was carried out using an instrument created and validated based on the guidelines of the Brazilian Association of Intensive Care Medicine. The analysis of the results was performed using statistical tests. Results: A total of 118 professionals participated, and nurses comprised 86%.There was a prevalence of females (77%); the average age was 37.4 ± 1.4 years, and the average length of experience was 8 ± 2 years. A total of 93% of participants stated that they knew and used the clinical management guidelines. However, the professionals’ performance related to specific questions directed at clinical management revealed an average error rate of 37.9%, with nurses showing a higher average, with 40.1% errors, compared to 19.9% for physicians. The question with the highest success rate (92.4%) was related to the recommended value for maintaining mean arterial pressure. In contrast, the question related to body temperature had the lowest number of correct answers (11%). Conclusion: Although a significant majority of participants claim to know and use the guidelines for maintaining potential organ donors, there are still important inconsistencies and heterogeneities regarding the recognition of the specific recommendations presented by the Brazilian Association of Intensive Care Medicine. The greatest decline in knowledge was associated with nurses. Investing in greater dissemination of the guidelines and in training professional teams seems to be the most viable way to improve this scenario.